Adjuvant chemotherapy after primary treatments for cervical cancer: a critical point of view and review of the literature. Issue 4 (April 2014) - Angioli, Roberto; Luvero, Daniela; Aloisi, Alessia; Capriglione, Stella; Gennari, Paolo; Linciano, Francesca; Li Destri, Marta; Scaletta, Giuseppe; Montera, Roberto; Plotti, Francesco
<x xml:space="preserve">Abstract</x> Cervical cancer is the second most frequent female malignancy worldwide. Concurrent chemoradiotherapy represents the standard of care for patients with advanced stage cervical cancer, while radical surgery (RS) and radiotherapy is widely used for treating early stage cervical cancer. However, the poor control of micrometastasis, declining operability, the lack of radiotherapy departments and the high incidence of long-term complications due to radiotherapy have brought about the development of different therapeutic approaches such as neoadjuvant chemotherapy followed by RS. Unfortunately, treatment results are still unsatisfactory due to a high recurrence rate and several authors have studied the possibility to add an adjuvant treatment to primary therapy. We reviewed the literature concerning the role of adjuvant chemotherapy in advanced cervical cancer after neoadjuvant chemotherapy followed by RS and after chemoradiotherapy.